Scrolling into Financial Despair: A Profile Study of Doomscrolling Among TikTok-Using University Students - Khoirur Reza; Syauqia Havelata Jihan; Michael Christianto; Naifa Rachman; Damajanti Kusuma Dewi (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This study explores the financial doomscrolling behavior of college students using the TikTok platform. Financial doomscrolling refers to the compulsive consumption of negative financial content, which may shape students’ perceptions of economic reality and influence their mental health. Using a descriptive quantitative method and survey approach, 190 active TikTok-using students aged 17–25 participated in this study. The Financial Doomscrolling Questionnaire (FDQ) was used to classify participants into high, medium, or low doomscrolling categories. Results revealed that the majority (72.11%) of participants showed a moderate level of financial doomscrolling, while 19.47% were in the high category. Second-year students displayed the highest number of high doomscrolling behaviors. This study provides a descriptive overview of the distribution patterns of doomscrolling behavior among college students. The explanation of doomscrolling dynamics is supported by Solso’s cognitive theory and Erikson’s psychosocial development theory, offering contextual insights into how students may process and relate to financial content online. It expands the discourse of doomscrolling beyond the pandemic context by highlighting financial content as a trigger for digital distress, and emphasizes the need for digital literacy-based psychosocial interventions among youth.